2006
DOI: 10.1093/aje/kwj365
|View full text |Cite
|
Sign up to set email alerts
|

Meta- and Pooled Analyses of the Cytochrome P-450 1B1 Val432Leu Polymorphism and Breast Cancer: A HuGE-GSEC Review

Abstract: The association between the cytochrome P-450 1B1 (CYP1B1) Val432Leu polymorphism and breast cancer was assessed through a meta-analysis of all published case-control studies and a pooled analysis of both published and unpublished case-control studies from the Genetic Susceptibility to Environmental Carcinogens (GSEC) database ( www.upci.upmc.edu/research/ccps/ccontrol/g_intro.html ). GSEC is a collaborative project that gathers information on studies of metabolic gene polymorphisms and cancer. Thirteen article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 58 publications
7
62
2
Order By: Relevance
“…These results are inconsistent with those reported for Asians in the meta-analysis. 24 Previous studies have demonstrated that the Val allele contributes to an increase in 4-hydroxylation activity and a lower urinary 2-OHEs/16a-OHEs ratio (Table 1), whereas the Leu allele contributes to an increase in procarcinogen activation. 2,16,34 Our results might be explained by the latter mechanism.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results are inconsistent with those reported for Asians in the meta-analysis. 24 Previous studies have demonstrated that the Val allele contributes to an increase in 4-hydroxylation activity and a lower urinary 2-OHEs/16a-OHEs ratio (Table 1), whereas the Leu allele contributes to an increase in procarcinogen activation. 2,16,34 Our results might be explained by the latter mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…2,24 A recent meta-analysis demonstrated that Val allele carriers have a lower risk of breast cancer than Leu/Leu carriers among women of mixed/African ethnicity, but that there is no difference in Asians. 24 In the present study, Val allele carriers tended to have a decreased risk in the three populations combined and a significantly decreased risk among JJ. These results are inconsistent with those reported for Asians in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the patterns of the CYP1B1 polymorphic marker (rs1056836, 4326C> G, L432V) genotype frequencies distribution has significant racial differences (20)(21)(22). For Asian populations (Chinese, Japanese, Mexicans) it is very typical to observe the predominance of CYP1B1*1*1 genotype, which varies from 67 to 91% (20).…”
Section: Discussionmentioning
confidence: 99%
“…For Asian populations (Chinese, Japanese, Mexicans) it is very typical to observe the predominance of CYP1B1*1*1 genotype, which varies from 67 to 91% (20). In contrast, for Africans the most frequent genotype is CYP1B1*3*3, 68% in African Americans with the level of 87% in the Yoruba in Ibadan, Nigeria, YRI (HapMap) (20,21).…”
Section: Discussionmentioning
confidence: 99%